DETERMINATION OF HABITAT 6270*_3 PERMITTED DRAINAGE RATE - Kaupuža, Renāte; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
Amelioration has dramatically altered the distribution of semi-natural grasslands in Latvia and as a result of the drainage, and the ocurrance of humid grassland habitats has decreased sharply. The aim of the paper was to identify drainage rate for habitat 6270*_3 ecohydrological requirements which is necessary for its successful management and long-term existence. The work looked at 15 equally managed (extensively grazed and/or mowed) perennial, natural grasslands at different levels of drainage resulting in various quality states. To reveal the most habitat-preserving drainage rate, for each site of the habitat 6270*_3 a decrease of groundwater table was identified. As a result a rate that meets ecohydrological requiremets is procured.